A visão bioética diante do comportamento social na evolução do tratamento da disfunção erétil - Abreu, Ana Carolina de (2015)
Since ancient times to nowadays, the Erectile Dysfunction has been considered a condition that has always affected men. It has been not only a reason for embarrassment, but also an issue of multifactorial cause related either to psychological or organic and drug factors. For this reason, a significant impact can be observed on the individuals quality of life and their partners while this is associated with low self-esteem, depression, difficult relationship and increased anxiety. As this issue is currently a bioethical matter, it is feasible and necessary to be solved. Its main focus is the principle of life protection; introduced into the Ethics of scientific progress and outlining the guiding and protective limits of the person. There is also the autonomy of the individual's will which has valued the man according to his own individuality as a human being with rationality and liberty. The majority of individuals are not well informed. They search also for easier or less embarrassing ways for treatment and solutions. As a result, it is up to them to choose, "searching for a skilled professional", or a searching for Websites, mysticisms and charlatan. Thus, this study by means of a search on databases such as Pubmed Index, Google and Google Scholar shows publications and data research approaching Erectile Dysfunction from 1930 to today.